Prioridades competitivas e inovação em pequenas empresas do setor metal mecânico: um estudo multicasos na região de Sorocaba - Lara, Felipe Ferreira de (2013)
It is believed that the production function must support the competitive strategy, offering an important contribution to the competitiveness of an organization. The production strategy, whose content is determined by competitive priorities and the structural and infrastructural decision areas, plays a fundamental role in this process and should be aligned with competitive strategy. Moreover, recognition of the importance of innovation and technology has intensified to the point of becoming one of the most representative items in a company. Thus, based on the importance of manufacturing strategy and innovation in the organizational context, this study aimed to analyze the influence exercised by competitive priorities in the occurrence of innovations in small companies of metal mechanic sector in Sorocaba/SP. Since small businesses have certain specific characteristics, the study aimed to analyze how these specificities influence the practice of competitive priorities and the occurrence of innovation. To collect and analyze the data, it was used a qualitative approach and method of multicase study. Among the main results, it was found that the quality, flexibility, delivery and cost proved, in that order of importance, as generators of innovation practices in the surveyed companies. The quality and flexibility were closely related to product and process technological innovations. In the case of non-technological innovations, quality influenced the organizational and marketing innovations. Regarding the characteristics of small businesses, as facilitating factors for the practice of competitive priorities and the adoption of innovations, it was observed the specificities centered on the figure of the owner, on internal organization and the influence of the environment. As factors that worked as barriers are related to the specificities centered on the influence of the environment, mainly, and the specific focus on internal organizational of the company.